2008
DOI: 10.1186/1750-1326-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in γ-secretase activity and specificity caused by the introduction of consensus aspartyl protease active motif in Presenilin 1

Abstract: Presenilin (PS1 or PS2) is an essential component of the active γ-secretase complex that liberates the Aβ peptides from amyloid precursor protein (APP). PS1 is regarded as an atypical aspartyl protease harboring two essential aspartic acids in the context of the sequence D257LV and D385FI, respectively, rather than the typical DTG...DTG catalytic motif of classical aspartyl proteases. In the present studies, we introduced the sequence DTG in PS1 at and around the catalytic D257 and D385 residues to generate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…AZD-3839 has 14 and >1000-fold greater selectivity over BACE2 and cathepsin D, respectively, and orally administrated AZD-3839 shows dose- and time-dependent lowering of plasma, brain, and CSF Aβ40, Aβ42, and sAPPβ levels in mouse (C57BL/6 WT mice), guinea pig, and non-human primate [ 42 ]. Interestingly, treatment with this compound showed a biphasic effect, which causes an initial small increase in Aβ levels followed by a subsequent significant reduction in Aβ, similar to our previous reports for γ-secretase inhibition [ 7 ]. It has also been reported that the IC 50 values to reduce Aβ40 in plasma were 64- and 48-fold lower than those in brains for mouse and guinea pig, respectively [ 42 ].…”
Section: Fragment-based Discovery Improves Bace1 Inhibitor Pharmacolosupporting
confidence: 87%
“…AZD-3839 has 14 and >1000-fold greater selectivity over BACE2 and cathepsin D, respectively, and orally administrated AZD-3839 shows dose- and time-dependent lowering of plasma, brain, and CSF Aβ40, Aβ42, and sAPPβ levels in mouse (C57BL/6 WT mice), guinea pig, and non-human primate [ 42 ]. Interestingly, treatment with this compound showed a biphasic effect, which causes an initial small increase in Aβ levels followed by a subsequent significant reduction in Aβ, similar to our previous reports for γ-secretase inhibition [ 7 ]. It has also been reported that the IC 50 values to reduce Aβ40 in plasma were 64- and 48-fold lower than those in brains for mouse and guinea pig, respectively [ 42 ].…”
Section: Fragment-based Discovery Improves Bace1 Inhibitor Pharmacolosupporting
confidence: 87%
“…7) without change in Notch at the S3 site cleavage (Fig. 8) that strongly points to conformation as a factor [419]. Catalysis resembles that of bacterial signal peptide peptidases (SPP) with a Gly-Asp 385 -X motif or polytopic type 4 prepilins [420][421][422] containing a conserved PAL motif [415].…”
Section: Obligatory Components Of C-scmentioning
confidence: 87%
“…Differing by 2 amino acids at the carboxy-terminus, the choice of Aβ40 and Aβ42 isoform production is determined by γ-secretase cleavage site selection (Carter et al, 2008; Durkin et al, 1999). Notably, while Aβ40 accounts for approximately 90% of secreted Aβ and is the most abundant species recovered from cerebrospinal fluid, it is Aβ42 that is the predominant insoluble amyloid isoform deposited in the brain (Iwatsubo et al, 1994).…”
Section: Discussionmentioning
confidence: 99%